Natural History of C282Y Homozygotes for Hemochromatosis - John P Wojcik; Mark R Speechley; Ann E Kertesz; Subrata Chakrabarti; Paul C Adams (Canadian Journal of Gastroenterology)
PURPOSE: To study the clinical outcomes of subjects who are homozygous for the C282Y mutation of the hemochromatosis gene.